Marie Curie and the discovery of radium - Steinke, Ann E. 1946-; Xavier, Roger (New York Barron's, 1987)
Examines the life of the scientist Marie Curie, her background, and her discovery of radium.
Classified separately.
Includes index.
Bibliography: p. 118.
Keywords: Curie, Marie -- 1867-1934 -- Juvenile literature; Curie, Marie -- 1867-1934.; Radium -- Juvenile literature; Chemists -- Poland -- Biography -- Juvenile literature; Chemists; Women -- Biography